Manajemen Supervisi Akademik Terhadap Kinerja Guru pada Masa Pandemi Covid-19 - Teguh Prayitno (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2023)
The purpose of this study was to study and analyze the management of Academic Supervision on  Teacher  Performance  during  the  Covid-19  Pandemic.  The  research  location  is  in  Sekolah  Aliyah  Negeri  2  Bandung.  This  research  is  a  research  using  a  qualitative  approach  and  the results  of  the  research  are  presented  in  a  descriptive  form.  Data  collection  in  this  study  was carried  out  by  means  of  interviews,  observation,  and  documentation.  The  results  showed: First,   the   Academic   Supervision   Management   at   SMP   Negeri   2 Cimenyam   Kabupaten  Bandung  for  several  components  is  in  accordance  with  the  theory  of  the  implementation  of covid  academic  supervision,  namely  (1)  Planning:  includes  review  of  supervision  programs, identification     of     infrastructure,     preparation     of     assessment     instruments,     program synchronization  and  socialization  program.  (2)  implementation:  includes  pre-observation activities   (initial  planning,   checking  learning  plans,   learning  media),   conducting  online learning   observations   through   media   /   applications,   and   conducting   post-observation activities   by   analyzing   the   results   of   observations,   evaluating   and   planning   follow-up supervision    (3)    Evaluation:    includes    the    activity    of    analyzing    the    results    of    the implementation  of  supervision  from  beginning  to  end  and  following  up  on  the  results  of  the supervision.  Second,  the  teacher's  performance  in  making  learning  planning  is  quite  good, some   components   still   need   to   be   improved,   and   for   the   assessment   of   learning implementation, it has not been maximally carried out,the new assessment is seen when there is a report on learning activities by the teacher.